Notched tensile strength of randomly oriented E-glass composite laminates - Govindan Potti P.K.; Nageswara Rao B.; Srivastava V.K. (My University, 2025)
A simple relation is used for the characteristic lengths to improve the accuracy while evaluating the notched tensile strength of E-glass composite laminates through Whitney-Nuismer fracture models. The analytical results are found to be in good agreement with existing test results. © 2000 Elsevier Science S.A.